(untitled) (Journal of Legal Sciences, 2026)
The use of artificial intelligence–powered technologies within the framework of international law represents a significant turning point in global efforts aimed at preventing and documenting crimes related to genocide, which is considered one of the most heinous crimes targeting humanity as a whole. Since the adoption of the 1948 Convention on the Prevention and Punishment of the Crime of Genocide, the primary challenge facing the international community has remained the ability to intervene early to prevent the commission of the crime, in addition to documenting it accurately in a manner that ensures the accountability of its perpetrators. Today, artificial intelligence offers advanced capabilities in monitoring hate speech, analyzing big data, and early detection of dangerous indicators, as well as enhancing the admissibility of digital evidence before international courts. However, these capabilities raise numerous legal and ethical issues, including the legality of AI-generated evidence, ensuring its neutrality and reliability, and the need to establish a regulatory legal framework governing its use. Consequently, this study aims to analyze this legal framework and explore mechanisms for its development in a way that achieves a balance between technological effectiveness and the protection of human rights.